개방형 축사의 암모니아 배출량 산정 방법 및 배출 특성 분석 - 노준영(Rho, Joon Young); 강성민(Kang, Seong Min); 김고은(Kim, Go Eun); 전의찬(Jeon, Eui-Chan) (한국기후변화학회지, 2021)
In this study, methods for estimating ammonia emissions in livestock houses were reviewed, and ammonia concentrations were measured and characteristics analyzed in chicken house. There are three major methods of calculating ammonia emissions of livestock houses, the Portable Monitoring Units (PMU) method, the Saraz Method for Determination of Ammonia Emissions (SMDAE), and the Tracer gas method. Comparing the average ammonia concentration of laying hen and broiler houses, that of broilers was higher than that of laying hens, but the effect of open winch curtain was greater than that of measurement time. The concentration of ammonia emission differed over time for laying hens and for broilers, and no consistent trend was found. The internal ammonia concentration of the closed operation type was higher than that of the open operation type, and the ammonia concentration increased with age of the chickens. KCI Citation Count: 0